2020
DOI: 10.3389/fonc.2020.01451
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of EGFL6 by CRISPR/Cas9 Mediated Inhibition of Tumor Angiogenesis in Ovarian Cancer

Abstract: Tumor angiogenesis plays an important role in the progression and metastasis of ovarian cancer. EGFL6 protein is highly expressed in ovarian cancer and has been proposed to play an important role in promoting tumor angiogenesis. Here, a CRISPR/Cas9 system was used to knockout the EGFL6 gene in the ovarian cancer cell line SKOV3, using specific guide RNA targeting the exons of EGFL6. The knockout of EGFL6 markedly inhibited the proliferation, migration, and invasion of SKOV3 cells, as well as promoted apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 48 publications
2
6
1
Order By: Relevance
“…Meanwhile, the PD‐L1/VEGFR2/FAK axis regulated the biological process of angiogenesis. Although other studies clarified the molecular mechanisms of ovarian cancer angiogenesis and metastasis [31, 32], the present study demonstrated that PD‐L1 could act upon VEGFR2, a membrane receptor, to induce ovarian cancer cell angiogenesis and metastasis.…”
Section: Discussioncontrasting
confidence: 67%
“…Meanwhile, the PD‐L1/VEGFR2/FAK axis regulated the biological process of angiogenesis. Although other studies clarified the molecular mechanisms of ovarian cancer angiogenesis and metastasis [31, 32], the present study demonstrated that PD‐L1 could act upon VEGFR2, a membrane receptor, to induce ovarian cancer cell angiogenesis and metastasis.…”
Section: Discussioncontrasting
confidence: 67%
“…One factor that has recently captured researchers' attention for its role in angiogenesis is epidermal growth factor-like domain-containing protein 6 (EGFL6) [23]. EGFL6 is a member of the EGF superfamily of proteins; it is also upregulated in tumorigenesis and epithelial-tomesenchymal transition [24][25][26][27]. Xu et al found that osteoblast-like cells secrete EGFL6 in a paracrine manner, triggering EC migration and angiogenesis through activation of the ERK pathway [28].…”
Section: Introductionmentioning
confidence: 99%
“…EGFL6 is a protein known to be highly expressed in ovarian cancer and proposed to play a key role in promoting tumor angiogenesis. Its knockout markedly inhibited the proliferation, migration, and invasion of SKOV3 cells, as well as promoted apoptosis of tumor cells by downregulating FGF-2/PDGFB signaling pathway [ 140 ].…”
Section: Crispr and Cancermentioning
confidence: 99%